2003
DOI: 10.1161/01.hyp.0000047877.36743.fa
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Renal Cytochrome P450 2C Enzymes and Impaired Vasodilation Are Associated With Angiotensin Salt-Sensitive Hypertension

Abstract: Abstract-Excess dietary salt intake differentially modulates the activity of cytochrome (CYP) P450 enzymes in kidney cortex. Exactly how increased angiotensin (Ang) II levels and hypertension change the regulatory effect of high salt on CYP450 enzymes remains unclear. The present study investigated the effects of combined administration of Ang II and a high-salt diet on P450 epoxygenase and hydroxylase protein levels in kidney, as well as afferent arteriolar responses to acetylcholine and sodium nitroprusside.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
117
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(132 citation statements)
references
References 42 publications
12
117
3
Order By: Relevance
“…3,4,38 Salt-sensitive hypertension has also been linked to an inability of the kidney to increase EET generation. 10,39 We provided additional evidence in this study that increasing epoxide-diol ratios ameliorated the renal injury associated with angiotensin salt-sensitive hypertension. We cannot separate the direct effects of increasing EET levels versus blood pressure effects on kidney damage because blood pressure decreased in angiotensin hypertensive animals treated with AUDA.…”
Section: Imig Et Al Epoxides and Angiotensin Hypertension 979mentioning
confidence: 56%
“…3,4,38 Salt-sensitive hypertension has also been linked to an inability of the kidney to increase EET generation. 10,39 We provided additional evidence in this study that increasing epoxide-diol ratios ameliorated the renal injury associated with angiotensin salt-sensitive hypertension. We cannot separate the direct effects of increasing EET levels versus blood pressure effects on kidney damage because blood pressure decreased in angiotensin hypertensive animals treated with AUDA.…”
Section: Imig Et Al Epoxides and Angiotensin Hypertension 979mentioning
confidence: 56%
“…21 To determine if an inability to upregulate the CYP2C and CYP2J isoforms was associated with the persistent hypertension after exposure to angiotensin II, we evaluated epoxygenase mRNA and protein expression in renal microvessels. Figure 2 and Figure 3 show representative Western blots and densitometric analysis of CYP2C11, CYP2C23, and CYP2J protein in renal microvessels.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown an impaired ability to upregulate renal epoxygenase enzymes in animal models of salt-sensitive hypertension. 20,21 In addition, kidney-specific downregulation of P450 epoxygenase enzymes is associated with hypertension and endorgan damage in transgenic rats overexpressing both human renin and angiotensinogen genes (dTGR). 26 We have previously reported that chronic angiotensin II infusion combined with a high salt diet was associated with decreased CYP2C11, CYP2C23, and CYP2J protein levels in renal vasculature and that this may contribute to the development of salt-sensitive hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 has been demonstrated to downregulate CYP epoxygenase enzymes [91,92]. There are increased IL-6 levels and an inability to increase renal CYP epoxygenase expression in angiotensin salt-sensitive hypertension [33,93]. A recent study utilizing IL-6 gene deficient mice has demonstrated protection from renal damage in hypertension and that the decrease in injury was associated with an increased CYP expoxygenase expression [33].…”
Section: Emerging Therapeutic Approaches For Epoxyeicosanoids and Renmentioning
confidence: 99%